Aspek Rasm, Tanda Baca, dan Kaligrafi pada Mushaf-mushaf Kuno Koleksi Bayt Al-Qur'an & Museum Istiqlal, Jakarta - Asep Saefullah (SUHUF, 2008)
To some extend, this writing is a library research. However, the primary sources is the ancient manuscripts (Qur'anic manuscripts) in the collection of Bayt Al-Qur’an & Museum Istiqlal, Jakarta. Some philological steps are used, in particular in the case of making inventory and manuscript description. This writing is an effort to observe and to analize some aspects of that ancient manuscript. Those aspects are as follow: (a) the aspect called rasm or the writing being used to rewrite and copy the manuscript; (b) reading symbols which consist of tajwid (the grammar of reading the Qur'an) and the sign of stopping the reading; and (c) calligraphy or khat (the art of Arabic writing). Considering that this kind of research is still rare, it is worth noting that this writing is still at the preliminary stage.